2022
DOI: 10.3892/mmr.2022.12819
|View full text |Cite
|
Sign up to set email alerts
|

Role of ROS‑mediated autophagy in melanoma (Review)

Abstract: Melanoma is the most aggressive form of skin cancer with the poorest prognosis and its pathogenesis has yet to be fully elucidated. As key factors that regulate cellular homeostasis, both reactive oxygen species (ROS) and autophagy are involved in the development of melanoma, from melanomagenesis to progression and drug resistance. However, the interaction between ROS and autophagy in the etiology and treatment of melanoma is not well characterized. The present review examined the production of ROS and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…NOX induces the intracellular accumulation of ROS. Research studies have shown that NOX is one of the sources of ROS in melanoma, playing a crucial role in all aspects of melanoma development [ 55 , 56 ]. Brevilin A (Brv-A), a sesquiterpene lactone compound of Centipeda minima induces ROS generation through NOX2 and NOX3 regulation [ 57 ].…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…NOX induces the intracellular accumulation of ROS. Research studies have shown that NOX is one of the sources of ROS in melanoma, playing a crucial role in all aspects of melanoma development [ 55 , 56 ]. Brevilin A (Brv-A), a sesquiterpene lactone compound of Centipeda minima induces ROS generation through NOX2 and NOX3 regulation [ 57 ].…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…Free radicals, characterized by one or more unpaired electrons, including ROS, play a detrimental role in various skin pathologies including skin carcinogenesis 35 . Excessive ROS production disrupts the redox balance, leading to oxidative stress, DNA damage, gene mutations, and increased cell proliferation, ultimately contributing to skin carcinogenesis 9 , 36 . The ability of SY to scavenge ROS suggests its potential to restore redox balance and confer protection against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that SY demonstrated antioxidant activity by protecting HaCaT cells from cytotoxicity, excessive ROS production, and mitochondrial dysfunction induced by tBHP. This is of particular significance considering that an imbalance in ROS formation leads to oxidative stress, which is implicated in oxidative DNA damage, skin pathologies and skin cancer development 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…B. bidum activated ROS during proliferating, which can alleviate certain cancers and promote tumor apoptosis and death, and accelerate autophagy through different pathways. 16,24,29 The morphological changes of tumor cells under an electron microscope might be direct evidence. The adsorption of B. bidum and classic enhanced permeability and retention (EPR) The HE staining results indicated that the tumor tissue in the B. bidum@CL-PFH-DOX-NPs + PFUS group had more severe damage, including nuclear fragmentation, dissolution, liquefaction, and vacuolization in the cytoplasm, even complete disappearance of cell structure, which was similar to the results by Wang et al 2 The apoptosis phenomenon was also notable in the B. bidum@CL-PFH-DOX-NPs + PFUS group compared with controls, suggesting a higher tumor-killing effect than that of B. bidum combined with PFUS or CL-PFH-DOX-NPs combined with PFUS.…”
Section: Discussionmentioning
confidence: 99%
“…B. bifidum activated ROS during proliferating, which can alleviate certain cancers and promote tumor apoptosis and death, and accelerate autophagy through different pathways. 16,24,29 The morphological changes of tumor cells under an electron microscope might be direct evidence. The adsorption of B. bifidum and classic enhanced permeability and retention (EPR) effect endowed CL-PFH-DOX-NPs with high affinity for the tumor, offering a foundation for the self-aggregation of B. bifidum and CL-PFH-DOX-NPs within the tumor.…”
Section: Discussionmentioning
confidence: 99%